The Concept of Women's Freedom of Thought: Analysis of the Emancipation Hadith, Historical Perspective of Asma' bint Yazid's Involvement in the Yarmuk War - Zuli Dwi Rahmawati; Damanhuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article examines the status of the hadith narrated by Muhajir above, especially from a review of the sanad? and what content is in it. From the discussion it can be concluded: 1). The hadith regarding the direct involvement of Asma' bint Yazid in the Yarmuk war was narrated by trusted people and the sanad is continuous. Therefore, this hadith is considered authentic lidzatihi. 2). Analysis of the hadith in relation to women's emancipation from the historical perspective of Asma' bint Yazid's involvement in the Yarmuk war indicates that Islamic history has provided references to the emancipation of women through Asma''s involvement in the war. Asma's descent into the battlefield was definitely based on careful thought and consideration, this falls within the realm of freedom to think about what will be done and the consequences faced. Implicitly, this hadith opens the shackles of Jahiliyah thinking to a modern direction that every person (without distinction of gender) can legitimately convey and implement the results of his thinking to the wider community because in reality there is no difference in freedom of thought except within the limits determined by the Shari'a.